Obraz i tekst. Na wysokiej górze. Commedia della lingua Krystyny Miłobędzkiej w ilustracjach Iwony Chmielewskiej - Wysłouch, Seweryna (Przestrzenie Teorii, 2022)
A fragment of Krystyna Miłobędzka’s theatre play for children Na wysokiej górze. Commedia della lingua (1990) was published separately (2014, 2017) as a work of both Krystyna Miłobędzka and Iwona Chmielewska, an author of picture books. Chmielewska tones down the word play in Miłobędzka’s text. Instead, she introduces images of the poet at different ages, depicted in contemplative poses, and presents the character’s epiphanic experience beyond time and space. The images and the text constitute separate, sylleptic sequences. The meditative atmosphere of Chmielewska’s illustrations adequately conveys the worldview of Miłobędzka – a “linguistic” poet, who refers to the poetry of the Far East.